PENGARUH LAYANAN PENDIDIKAN AGAMA DI SEKOLAH TERHADAP RELIGIUSITAS SISWA: STUDI EXPOST FACTO DI MEDAN - Suhardin Suhardin; Hayadin Hayadin (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2017)
ABSTRACTThe objective of this research to find out the effect of the level religious educational service with the religiusitas student. The research was conducted in SMA/SMK Government and non Government in theÂ  Medan Nort Sumatera using 1X2Â  design involving 22 schools chosen by using purposive random sampling.The data analysis and interpretation indicated that: There is not difference religiusitas value student in the school have religious educational service high between the school have religious educational service low. The conclusion the level school has religious educational service not effect againt religiusitas student value.